A significação da charge sob as categorias de análise da semiótica Peirciana - MORAES, Simone Alcântara (2019)
The present article proposes to verify the applicability of the semiotic theory, in the charge sign. It was sought from the concepts of signs of Peirce (2005), and in the studies of Santaella (1983), (2002), to apply such categories in two cartoons. Thus, in the sign, the relation with its object, which presents the triadic relations that the semiotic experience contemplates are the aspects: iconic, initial, and symbolic.